Nutation terms adjustment to VLBI and implication for the Earth rotation resonance parameters. Issue 2 (17th October 2019) - Nurul Huda, I; Lambert, S; Bizouard, C; Ziegler, Y
SUMMARY: The nutation harmonic terms are commonly determined from celestial pole offset series produced from very long baseline interferometry (VLBI) time delay analysis. This approach is called an indirect approach. As VLBI observations are treated independently for every session, this approach has some deficiencies such as a lack of consistency in the geometry of the session. To tackle this problem, we propose to directly estimate nutation terms from the whole set of VLBI time delays, hereafter referred as a direct approach, in which the nutation amplitudes are taken as global parameters. This approach allows us to reduce the correlations and the formal errors and gives significant discrepancies for the amplitude of some nutation terms. This paper is also dedicated to the determination of the Earth resonance parameters, named polar motion, free core nutation, and free inner core nutation. No statistically significant difference has been found between the estimates of resonance parameters based upon 'direct' and 'indirect' nutation terms. The inclusion of a complete atmospheric-oceanic non-tidal correction to the nutation amplitudes significantly affected the estimates of the free core nutation and the free inner core nutation resonant frequencies. Finally, we analyzed the frequency sensitivity of polar motion resonance and found that this resonance is mostly determined by the prograde nutation terms of period smaller than 386 d.